Role of Macrophages in the Progression and Regression of Vascular Calcification - Li, Yalan; Sun, Zhen; Zhang, Lili; Yan, Jinchuan; Shao, Chen; Jing, Lele; Li, Lihua; Wang, Zhongqun (Frontiers in Pharmacology, 2020)
Vascular calcification is an abnormal cell-mediated process in which bone-specific hydroxyapatite crystals are actively deposited on the blood vessel wall and is a significant pathological basis for the increased incidence and mortality of adverse cardiovascular events. Macrophages play an important regulatory role in the occurrence, development and regression of vascular calcification. After the tissue microenvironment changes, macrophages subsequently change their polarity and phenotype or secrete functional substances as an adaptive response. As research on macrophages continue to move into this field, we gain a new understanding of the mechanism of the formation and regression of vascular calcification, which might offer valuable new intervention targets for the prevention and inhibition of vascular calcification. This review summarizes a wealth of research in this field and explores the roles of macrophages in the development process of vascular calcification.